Avaliação do estresse de surdos ao falar em público - Santos, Warley Almeida [UNIFESP] (2019)
Objective: We aimed to evaluate the stress in Brazilian Sign Language users and hearers upon a public speech test.Methods: 23 male individuals were recruited, 10 of which had the hearing impaired and were fluent in Brazilian Sign Language and 13 of which were hearers that did not know Brazilian Sign Language. The age of the participants varied from 18 to 30 years, all participants were students of popular preparatory courses for college entrance examination. On the day of the test, we evaluated basal parameters that consisted in the collection of saliva for the assessment of cortisol, amylase activity, assessment of cardiac frequency and endothelial function. Subsequently, the participants were led to an auditorium with a previously seated audience. In this room, the participants watched a video with audio and translation to Brazilian Sign Language about diabetes. Afterwards, we asked the volunteers to explain to the audience their understanding about the video. At the end, a person from the audience made an oral question for this participant. Immediately after these steps, the participants were led to the initial room for the measurement of the same initial parameters and to respond to a questionnaire about their self-perception of stress.Results: The basal cortisol of the hearing impaired group was lower, accompanied by a better endothelial response. No significant differences were observed in the other parameters. After the public speech test, an statistically significant increase in cardiac frequency was observed in both groups. No statistically significant difference in arterial pressure was observed between both groups. No statistical differences between groups were observed regarding salivary cortisol in posttest samples. Conversely, the activity of alpha amylase was increased by 30% in the hearing impaired group when compared to the hearing group after the public speech test. Moreover, the results in the self-perception stress test showed that psychologically the hearing impaired group displayed 390% in agitation, 790% in tension and 400% relative to the control group regarding preoccupation in the anxiety and stress parameters. Conclusion: Our data suggest that the hearing impaired individuals display higher stress when speaking in public and that this phenomenon may be recurrent in the routine of hearing impaired individuals. This, in part, may justify the lower values of basal cortisol and basal cardiac frequency observed.